KONTEN ILEGAL (ILLEGAL CONTENT): SEBUAH TINDAK PIDANA MENURUT UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Indah Sari (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2024)
Illegal Content is a criminal act related to illegal activities in the cyberspace. Electronic Crimes Act and Illegal Content are regulated in the Electronic Information and Transactions Law. Illegal Content is an action that involves inputting data or information to the Internet unethically, deceptive, violates the law or disturbs public order and considered as cybercrime. Many forms of it are fake news, defamation, pornography, or sharing information that classified as government secret, agitation, and propaganda against the present government, and so on. Illegal Content can also be explained as the activity of distributing (uploading, writing) false or prohibited content that can harm other people and violates the cyberlaw. The formulation of the problems in this writing is as follows: first, what is the difference between Illegal Content and Electronic Crimes Act according to Electronic Information and Transactions Law (ITE Law)? Second, what are the forms of Illegal Content according to Electronic Information and Transactions Law (ITE Law)? The kind of typing that the writer uses in this research is descriptive research (describing an object and taking simple conclusion from it) with secondary data and use statute approach, case approach, and conceptual approach. This kind of technique is collected by library researchÂ  and the data will be analyzed qualitatively.The purpose of this writing is to differentiate between Illegal Content and Electronic Crimes Act and explain the forms of Illegal Content based on the Electronic Information and Transactions Law.Â Keywords: Cyberspace, Cybercrime, Cyberlaw, Electronic Information and Transactions Law, Illegal Content.